2012
DOI: 10.1029/2012gl052514
|View full text |Cite
|
Sign up to set email alerts
|

Towards a universal criteria for turbulence suppression in dilute turbidity currents with non‐cohesive sediments

Abstract: [1] Turbidity currents exhibit fascinating physics as their sustained propagation depends on a tight interplay between the suspended sediments and turbulence. If resuspension dominates over deposition the intensity of the flow will increase, while if deposition dominates the flow turbulence can be completely damped inducing rapid settling of sediments and, eventually, flow extinction. This work explores the phenomenon whereby turbulence in a dilute turbidity current with non-cohesive sediments is abruptly exti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…Dutta (2012) showed that increase in eitherṼ or Ri τ increases the degree of self-stratification caused by suspended sediment and the extent to which a flow will stratify depends on the parameter V Ri τ . Cantero et al (2012) made similar observations for turbidity currents. In Figs. 2 and 3 the mean streamwise velocity, steady-state sediment concentration profile and normalized wall-normal turbulence intensity for set1 and set2 have been plotted.…”
Section: Channel Flow Configurationsupporting
confidence: 68%
“…Dutta (2012) showed that increase in eitherṼ or Ri τ increases the degree of self-stratification caused by suspended sediment and the extent to which a flow will stratify depends on the parameter V Ri τ . Cantero et al (2012) made similar observations for turbidity currents. In Figs. 2 and 3 the mean streamwise velocity, steady-state sediment concentration profile and normalized wall-normal turbulence intensity for set1 and set2 have been plotted.…”
Section: Channel Flow Configurationsupporting
confidence: 68%
“…The turbulence extinction threshold of Cantero et al (2009Cantero et al ( , 2011Cantero et al ( , 2012 is virtually identical to = 1 (Fig. 3b).…”
Section: Previous Formulationsmentioning
confidence: 71%
“…An apparent reduction in turbulence with increasing particle concentration is the result of a portion of this budget having been expended in maintaining particle suspension (Tilston, 2016). Both Bennett et al (2014) and Cantero et al (2012) invoke a similar expenditure of turbulent kinetic energy (TKE), arguing that part of the TKE is consumed or transferred from turbulent fluid to particles in order to keep them suspended. The interpretation presented here differs slightly in that we argue that the presence of suspended particles prevents part of the turbulence from ever being produced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations